2019
DOI: 10.1007/s42452-019-1783-7
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation analysis of Hall current effect on MHD micropolar fluid flow with rotation effect

Abstract: Entropy generation in form of heat dissipation destroys useful energy which accounts for the underperformance and decrease in the thermodynamic efficiency of a system. Since micropolar fluid is used as a working fluid in many technological and industrial processes, it is therefore necessary to examine the influence of all factors that can enhance entropy production so as to achieve the best energy systems design. In this paper, the influence of Hall current and ion-slip on the entropy generation rate of microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Here, it this exploration, it is reported that fluid temperature diminishes on augmenting the hall parameter. The impact of Hall current and ion slip parameter on a micropolar fluid past a vertical duct is discussed by Opanuga et al 37 . It is perceived that primary and secondary velocity rises on enhancing the Hall effect parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it this exploration, it is reported that fluid temperature diminishes on augmenting the hall parameter. The impact of Hall current and ion slip parameter on a micropolar fluid past a vertical duct is discussed by Opanuga et al 37 . It is perceived that primary and secondary velocity rises on enhancing the Hall effect parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady flow of this viscous fluid with variable viscosity and convective cooling is further investigated by Chinyoka and Makinde [23]. Other interesting results arising from the second-law analysis are discussed by Adesanya et al [24], Dalir et al [25], and Opanugat et al [26]. In all these studies, the researchers argued that it is essential to carry out such entropy production analysis to be able to measure the quantity of energy available for work during the convection in fluid flow with the view to upgrade the performance of the system.…”
Section: Introductionmentioning
confidence: 92%
“…Transformation rules theorems are applied on the governing differential equation and corresponding the boundary conditions of the system (see Tables 1 and 2) to obtain a set of recurrence relations equations in terms of the differential transforms of the original unknown variables and the expressions of these differential transforms when substituted into the corresponding inverse formulae give the desired finite series solution of the problem. Some of the studies featuring this method was discussed by Opanuga et al [26], Ayaz [30], Mohammadyari et al [31].…”
Section: Solution Technique and Validationmentioning
confidence: 99%
“…35 Analysis of irreversibility of a nanomaterial in a space between parallel pipes in the existence of magnetic field was done by Barnoon et al 36 Gireesha et al 37 deliberated the impression of magnetic field on a magnetohydrodynamic flowing of a nanomaterial with Newton boundary constraints and Darcy-Forchheimer rule were employed. The consequence of ion-slip effects irreversibility in an MHD micropolar liquid flowing with rotating effect and the outcome shows that entropy production decreases as in the enhancement of magnetic parameter were explored by Opanuga et al 38 The combined effect of magnetic field and ohmic dissipation on heat and mass transfer flow of nanofluid over a cone discussed by Upreti et al 39 Singh et al 40 numerically investigated the combined effect of magnetic field and slip on micropolar fluid flowing through a porous wedge with Hall and ion-slip. Shafiq et al 41 made an analysis on numerical modeling for bioconvective nanofluid with the magnetic field over a vertical stretching plate.…”
Section: Introductionmentioning
confidence: 99%